Analisis Strategi Pencapaian Kualitas Pendidikan Di Masa Pandemi Corona Virus Desease 19 Pada Politeknik Penerbangan Palembang - Emiyani, Johny; Nawawi, Effendi; Santoso, Anang Dwi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The research entitled Analysis of Education Quality Achievement Strategies During the Corona Virus Disease 19 Pandemic at the Palembang Aviation Polytechnic aims to identify and analyze education and training strategies during the Corona Virus Disease (Covid - 19) Pandemic in order to achieve quality education at the Palembang Aviation Polytechnic. This study uses a qualitative approach, which is a research procedure that aims to describe certain circumstances, which are described in separate words or sentences to obtain conclusions. The focus of the research in this study is the Analysis of Strategies for Achieving Quality of Education During the Corona Virus Disease 19 Pandemic at the Palembang Aviation Polytechnic. The data analysis technique used is qualitative data analysis techniques, while the data collection techniques used are observation, interviews and documentation. The results of the study show Strengths: Accreditation and certification that has been owned by the Palembang Aviation Polytechnic have met the requirements in accordance with the needs of the world of work with the certification provided by the Directorate General of Civil Aviation, in addition to educators who have competence according to the field of science. LMS as a learning system that supports the optimization of student knowledge in learning. Weaknesses: The need for a large budget for the maintenance and development of learning infrastructure equipment in accordance with the needs of the world of work that must be improved. Opportunities: The need for new personnel or human resources in the operation of the latest equipment in accordance with the needs of the work in solving existing problems Palembang Aviation Polytechnic can increase graduates and competencies based on the operation of the latest equipment in aviation. Threats: Some of the threats felt by the Palembang Aviation Polytechnic where infrastructure and technology facilities are also owned by several institutions and other agencies so that the competitiveness of graduates will increase.